Managing financial information in the trade lifecycle : a concise atlas of financial instruments and processes - Groot, Martijn (Elsevier world capital markets series., 2008)
Managing Financial Information in the Trade Lifecycle discusses the present and future of financial data management by focusing on the lifecycle of the financial instruments (stocks, bonds, options, derivatives) that generate and require data to keep the markets moving. This book is a concise reference manual of the financial information supply chain and how to maximize effectiveness and minimize cost. *First book fully dedicated to financial information supply chain and how to manage it effectively *Addresses hot topics that readers need to know: regulatory reporting regulations, data pooling, hubs, and data excahnges *Draws from actual lessons learned and presents many real-life scenarios of the business.